Program Literasi Sekolah terhadap Kemampuan Membaca dan Menulis pada Siswa Kelas V SDN 01 Cimangeunteung - Riri Asri Juniartrinur; Mutiara Zahra Khairunnisa; Ririn Mahera; Dine Trio Ratnasari (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2025)
This research was motivated by reading and writing literacy difficulties among fifth-grade students at SDN 01 Cimangeunteung, such as phoneme-grapheme comprehension deficits and reading fluency issues. The objective was to enhance these skills through the School Literacy Program (PLS). The research employed Classroom Action Research (CAR) design across two cycles. The population and purposive sample comprised 26 fifth-grade students. Instruments included student activity observation, literacy tests, and reflective notes, analyzed using quantitative descriptive techniques. Results indicated student activity improvement from 73% (Cycle I) to 92% (Cycle II), with average scores rising from 53.46 (46.15% mastery) to 70.58 (92.31% mastery). The study concludes that PLS effectively addresses literacy challenges via cyclic approaches and motivational rewards.